2018
DOI: 10.1016/j.jval.2018.09.1745
|View full text |Cite
|
Sign up to set email alerts
|

Pms31 - Secukinumab as a More Eeficient Alternative for Ankylosing Spondylitis Treatment: A Cost Per Responder Analysis From Korean Perspective

Abstract: OBJECTIVES: Compare costs associated with treatment for acute or degenerative medial meniscus tears. METHODS: Prospective, non-randomized, open-label, 24month observational surveillance study conducted between January 2011 and December 2014 at a single institution, approved by hospital Institutional Review Board, and with patient informed consent. Patients (n¼50) initiated into conservative (non-surgical) therapy or a surgical partial meniscectomy based on clinical assessment following physical examination and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Model-based budget impact analyses in Italy [ 49 ], Finland [ 51 ], Greece [ 52 ] and Brazil [ 53 ] also demonstrated that secukinumab is a cost-saving option for the treatment of AS. In cost-effectiveness analyses in Portugal [ 54 ], Tunisia [ 55 ] and Korea [ 56 ], the costs per responder were lower with secukinumab than with adalimumab in patients with AS.…”
Section: Place Of Secukinumab In the Management Of Ankylosing Spondylmentioning
confidence: 99%
“…Model-based budget impact analyses in Italy [ 49 ], Finland [ 51 ], Greece [ 52 ] and Brazil [ 53 ] also demonstrated that secukinumab is a cost-saving option for the treatment of AS. In cost-effectiveness analyses in Portugal [ 54 ], Tunisia [ 55 ] and Korea [ 56 ], the costs per responder were lower with secukinumab than with adalimumab in patients with AS.…”
Section: Place Of Secukinumab In the Management Of Ankylosing Spondylmentioning
confidence: 99%